2019
DOI: 10.1051/bioconf/20191201009
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of treated wastewater in viticulture: Can it be an alternative source of nutrient-rich water?

Abstract: Water scarcity is a global problem, which leads to unprecedented pressure on water supply in arid and semi-arid regions. Treating wastewater is an alternative and valuable water resource, therefore its reuse for agricultural irrigation has been growing worldwide since the beginning of the 21st century. In several regions of the wine-producing countries subject to significant water stress (e.g., Australia, California-USA, Spain), wastewater recycling appears to be the most accessible alternative, both financial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Wine-producing countries, in particular those subject to significant water stress, are today exploring this alternative, as wastewater recycling appears to be both financially and technically sustainable. It is pointed as a strategy of water management with high added value [48]. Even though water recycling and reuse can be implemented by almost any country, in Europe a small percentage of treated wastewater is being reused.…”
Section: Water Reuse and Recyclingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wine-producing countries, in particular those subject to significant water stress, are today exploring this alternative, as wastewater recycling appears to be both financially and technically sustainable. It is pointed as a strategy of water management with high added value [48]. Even though water recycling and reuse can be implemented by almost any country, in Europe a small percentage of treated wastewater is being reused.…”
Section: Water Reuse and Recyclingmentioning
confidence: 99%
“…It is therefore important to ensure that the quality of the reused water is suitable for the intended purpose (irrigation, washing, cleaning, pH adjustment, fire protection, cooling or heating purposes), and that it does not harm the environment or public health when discharged. On the other hand, even though ensuring WW microbiological quality is essential, care should also be taken for not reducing its nutrients (mainly N, P and K) as valuable inputs [48]. Another parameter being measured for this indicator also focus on nutrient recirculation and recovery technologies (classified as KSI as indicator 9C of circularity index is used).…”
Section: Water Reuse and Recyclingmentioning
confidence: 99%
“…11,53,57,59,61,62 These include macronutrients such as nitrogen compounds, phosphorus and potassium, which contribute to plant tissues growth, roots development, photosynthesis and protein synthesis. 25,62,63 The presence of these elements in water must be controlled as at high concentrations they can hamper crops growth. The variations in Ca 2+ , Mg 2+ , K + , Na + are similar to those found by Senou and al.…”
Section: Disscusionmentioning
confidence: 99%
“…Vineyards can be irrigated by waste water. Etchebarne suggests that in order to maintain quality, especially for the wine grape, growers should maintain a perfect balance between fertilizing factors which are responsible for water quality [48]. We carried out an experiment on water quality and compared their study with other ones derived from the bibliography and showed that the nutrients concentrations and contents of the water could be directly linked to wastewater origins.…”
Section: Irrigating Vineyards Using Wastewatermentioning
confidence: 99%